Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.4467/23539496ib.18.012.9385
|View full text |Cite
|
Sign up to set email alerts
|

Ocena bezpieczeństwa żywnościowego i samowystarczalności żywnościowej Polski na tle państw Unii Europejskiej

Abstract: The issues presented in the article show that the EU as a whole ensures food security; however, there are significant differences between individual countries.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 0 publications
0
3
0
1
Order By: Relevance
“…But in Poland, similarly to other developed countries, the problem of food insecurity is rather neglected in scientific research, especially at the household level. There are some papers focused on the food situation at the country level in comparison to other countries [44][45][46]. Considering the household food situation, there are some reports devoted mainly to the situation of children.…”
Section: Introductionmentioning
confidence: 99%
“…But in Poland, similarly to other developed countries, the problem of food insecurity is rather neglected in scientific research, especially at the household level. There are some papers focused on the food situation at the country level in comparison to other countries [44][45][46]. Considering the household food situation, there are some reports devoted mainly to the situation of children.…”
Section: Introductionmentioning
confidence: 99%
“…Both emergency and long-term food aid play a significant role in reducing the food gap in countries experiencing persistent food deficits. The long-term determinants of national food security are the continuity of the food supply stream, the rational management of natural resources, environmental and climatic factors, and the administrative and socio-political environment [24]. It is evident that ensuring national food security and reducing regional inequalities is pivotal in addressing global food problems.…”
Section: Food Security and Cereal Production In Europementioning
confidence: 99%
“…According to J. Clapp [55], "...Determining how trade fits into the food self-sufficiency policies of individual countries requires further refinement of the definition of the concept and clarification with respect to how it guides government policy choice". In a broader view, which the authors identified with in this work, the food self-sufficiency of a country is understood as the ability of the entire economy-that is, both agriculture, food industry, and other sectors in the country (including trade)-to meet the national demand for food [56]. Some authors define selfsufficiency from the point of view of the amount of kcal supplied [57].…”
Section: Interpretation Of the Basic Economic Categories Used In This Papermentioning
confidence: 99%